A Comparative review on ginger and garlic with their pharmacological Action - Daharia, Anju; Kumar Jaiswal, Vinod; Royal, Kabya Pratap; Sharma, Himanshu; Kumar Joginath, Anuj; Kumar, Roshan; Saha, Purabi (Asian Journal of Pharmaceutical Research and Development, 2022)
It is a therapeutic aspect of medicinal herbs mentioned here. Herbal plants can treat various diseases and ailments—the list of antioxidant included antioxidant, anti-inflammatory, anti-rheumatic, and circulation enhancer. It would be of great benefit in medical and surgical treatment. Those are fantastic. The promotion of the health system is easier, with medicinal plants than synthetic drugs.